2015
DOI: 10.1051/0004-6361/201425251
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic He-sdB pulsator LS IV-14°116: new insights from the VLT

Abstract: The intermediate helium subdwarf B star LS IV-14 • 116 is a unique object showing extremely peculiar atmospheric abundances as well as long-period pulsations that cannot be explained in terms of the usual opacity mechanism. One hypothesis invoked was that a strong magnetic field may be responsible. We discredit this possibility on the basis of FORS2 spectro-polarimetry, which allows us to rule out a mean longitudinal magnetic field down to 300 G. Using the same data, we derive the atmospheric parameters for LS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 40 publications
(61 reference statements)
3
45
0
Order By: Relevance
“…Comparing our predictions with the pulsational properties of known pulsating subdwarfs with mixed H+He surface compositions, namely LS IV-14 ∘ 116 with observed periods P ≃ 1950 − 5080 s (T e = 35150 ± 111, log g = 5.88 ± 0.02, log n(He)/n(H) = −0.62 ± 0.01, Randall et al 2015;Ahmad et al 2005;Green et al 2011), KIC 1718290 with P ≃ 1 − 12h (T e = 22100, log g = 4.72, log n(He)/n(H) = −0.45, Østensen et al 2012) and UVO 0825+156 with P ≃ 10.8 − 13.3h (T e = 38900 ± 270, log g = 5.97 ± 0.11, log n(He)/n(H) = −0.57 ± 0.01, Jeffery et al 2017), we found that their values of T e , log g, and log n(He)/n(H) (Figure 2) are well reproduced by our theoretical predictions. Quantitatively, however, the observed periods in these stars are systematically longer than the predicted ones (200 − 2000 s).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Comparing our predictions with the pulsational properties of known pulsating subdwarfs with mixed H+He surface compositions, namely LS IV-14 ∘ 116 with observed periods P ≃ 1950 − 5080 s (T e = 35150 ± 111, log g = 5.88 ± 0.02, log n(He)/n(H) = −0.62 ± 0.01, Randall et al 2015;Ahmad et al 2005;Green et al 2011), KIC 1718290 with P ≃ 1 − 12h (T e = 22100, log g = 4.72, log n(He)/n(H) = −0.45, Østensen et al 2012) and UVO 0825+156 with P ≃ 10.8 − 13.3h (T e = 38900 ± 270, log g = 5.97 ± 0.11, log n(He)/n(H) = −0.57 ± 0.01, Jeffery et al 2017), we found that their values of T e , log g, and log n(He)/n(H) (Figure 2) are well reproduced by our theoretical predictions. Quantitatively, however, the observed periods in these stars are systematically longer than the predicted ones (200 − 2000 s).…”
Section: Discussionsupporting
confidence: 54%
“…Coloured points correspond to models with excited modes and the colour coding shows the minimum e-folding time for each model. Also shown for comparison is the location of the known He-rich hot subdwarf pulsators LS IV-14 ∘ 116 (Randall et al 2015), UVO 0825+15 (Jeffery et al 2017), and KIC 1718290 (Østensen et al 2012). This trend is more notorious for the long-period limit.…”
Section: Periods Of Excited Modesmentioning
confidence: 99%
“…Its uncertainty is much lower than the symbol size. the equations of Randall et al (2014) by varying the position and velocity components within their respective errors by A96, page 7 of 9 applying a Monte Carlo procedure with a depth of 100 000. The distance of the sun from the Galactic centre was assumed to be 8.4 kpc.…”
Section: Photometric Distance and Space Velocitymentioning
confidence: 99%
“…So far, there has been no entirely satisfactory explanation for the pulsations observed. Quite intriguingly, it was recently shown to be a halo object (Randall et al 2015), which may indicate a distinct evolutionary history compared to the garden variety sdB stars. The second unique object is V499 Ser (often referred to as SDSS J160043.6+074802.9 in the literature), a hot (T eff ∼ 68 500 K according to Latour et al 2011) He-rich sdO star that exhibits very rapid multi-periodic oscillations with periods between 60 and 120 s (Woudt et al 2006).…”
Section: Introductionmentioning
confidence: 99%